Electrical performance characterization of helium inlet of the ITER PF6 coil double pancakes. (June 2020) - Xie, Y.; Song, Y.; Wu, H.; Lu, K.; Wei, J.; Shen, G.; Wu, W.; Yu, X.; Hu, B.; Wang, C.; Readman, P.; Sborchia, C.; et al.
Highlights: A thermal cycling test from 280 K to 77 K of the helium inlet trial mock-up of ITER PF6 coil was performed. Before and after the thermal cycling, a turn-to-turn DC HV test of the helium inlet trial mock-up was performed. Before and after the thermal cycling, a Paschen test of the helium inlet trial mock-up was performed. Abstract: The helium inlet is one of the most important components of the ITER Poloidal Field (PF) coils. The insulation structure of the helium inlet is critical to provide sufficient electrical and mechanical properties for a practical application. In this paper, an ITER PF6 coil double pancake helium inlet trial mock-up was designed and manufactured by simulating the actual manufacturing process. A thermal cycling test on the sample was carried out from 280 K to77 K, also before and after the thermal cycling, a turn-to-turn DC HV test and Paschen test were performed. The test results satisfied the ITER requirements. It has therefore been verified that the PF6 coil double pancake helium inlet insulation has good electrical properties, and can be applied to the formal production of the PF6 coil double pancakes.